Relationship between single nucleotide polymorphism of NOS2 gene and inheritance of allergic rhinitis in children - Wu, Xionghui; Zhao, Sijun; Huang, Weiqing; Huang, Min; Xie, Jiang; Liu, Guangliang; Chang, Shuting (Frontiers in Genetics, 2023)
Allergic rhinitis is a common chronic disease, and its high incidence has a great negative impact on the quality of life of many people, especially children. In this paper, through in-depth analysis of NOS2 gene polymorphism, the protective mechanism of NOS2 gene against AR was studied to provide theoretical and scientific basis for the diagnosis of children with AR. It was concluded that the concentration of Immunoglobulin E (IgE) in rs2297516 was 0.24 IU/mL compared with that in normal children. rs3794766 specific IgE concentration in the children group was increased by 0.36 IU/mL, which was higher than that in the healthy children group; the difference of rs7406657 specific IgE concentration between the children group and the healthy group was 0.03 IU/mL. The total serum IgE concentration in the healthy children group was lower than that in the infant group, and the change of Rs3794766 was the least, followed by rs2297516 and rs7406657. This means that rs7406657 is the highest, rs2297516 had general genetic correlation with AR patients, and rs3794766 had the least genetic correlation with AR patients. Among the three groups of SNP loci, the healthy children group was higher than the patient children group, indicating that AR reduces the gene frequency of the three loci, and the reduction of gene frequency will also increase the susceptibility of children to AR, because the frequency of gene occurrence will affect the gene sequence. In conclusion, smart medicine and gene SNPS can promote the detection and treatment of AR.